Model Pengembangan Pembangkit Listrik Tenaga Panas Bumi (PLTPB) untuk Industri Pariwisata di Daerah Lereng Gunung Ungaran Jawa Tengah - Juwitasari, Rena; Sukarjo, Heribertus; Setiadi, Hari (Proklamasi 45 University, 2024)
Mount Ungaran which is located in Central Java province potential for utilization of geothermal energy. Seen the discovery several geothermal manifestations example fumarole and hot springs. The temperature of the reservoir reached > 2250 C allows to do utilization of electrical energy around the area. In addition to its geothermal energy area around Mount Ungaran is the natural tourism potential, there are five object tourism around Mount Ungaran namely hot springs consist of Temple Gedongsongo, Nglimut, Umbul Sidomukti, Kendalisodo and Diwak . To reduce the burden of the Government against a coal-fired power supply as well as increase the independence of the energy sector for the industry, then the existence of this energy source can be utilized more broadly to support the activities of the industry, in particular the tourist industry that area around the slopes of Mount Ungaran. The results of the analysis showed that geothermal Gedongsongo worth in subtitution of the Power of Plant coal. Geothermal power plant scale pico (5kWe - 10 kWe) can be utilized in geothermal field Gedongsongo and can reach out to the surrounding area five object tourism slopes of Mount Ungaran.